I am attempting to solve the following problem:

Let $ A$ be the set of partitions of $ n$ with elements $ (a_1, \dots, a_s)$ such that $ a_i > a_{i+1}+a_{i+2}$ for all $ i < s,$ taking $ a_{s+1} = 0.$ Define $ g_n = F_{n+2}-1$ and let $ B$ be the set of partitions of $ n$ as $ b_1 \ge \dots \ge b_s$ such that $ b_i \in \{g_n\}$ for all $ i,$ and if $ b_1 = g_k$ for some $ k,$ then $ g_1, \dots, g_k$ all appear as some $ b_i.$ Prove $ |A|=|B|.$

**Attempt:** Let $ e_i$ be the vector with $ 1$ at position $ i$ and $ 0$ elsewhere. If $ b_1 = g_k,$ let $ c=(c_k, \dots, c_1)$ count how many times $ g_i$ appears. We calculate $ f: B \to A$ as follows:

Let $ c=(c_k,\dots,c_1), a=(0,\dots,0).$ While $ c \ne 0,$ let $ d_1 > \dots > d_k$ be the indices such that $ c_{d_i} \ne 0.$ Replace $ c, a$ with $ c-(e_{d_1}+\dots+e_{d_k}), a+(g_{d_1} e_1 + \dots + g_{d_k} e_k)$ respectively. After the while loop ends, let $ f(b)=a.$

Let $ \sum a, \sum b, \sum c$ be the sum of the components of $ a, b, c$ respectively. Since $ \sum c$ decreases after every loop, the algorithm terminates and $ f(b)$ is well-defined. Since $ c_k g_k + \dots + c_1 g_1 + \sum a$ does not change after every iteration, is $ \sum b$ at the start and $ \sum a$ at the end, we have $ \sum f(b) = \sum b = n,$ so $ f(b)$ is also a partition of $ n.$ Now $ a = (g_k, \dots, g_1)$ after the first loop, which satisfies the condition $ g_i > g_{i-1}+g_{i-2}$ since $ g_i = F_{n+2}-1 = (F_{n+1}-1)+(F_n-1)+1 > g_{i-1}+g_{i-2}.$ Furthermore, after every iteration of the loop, the difference $ a_i – (a_{i-1}+a_{i-2})$ changes by $ 0, g_{d_j}-g_{d_{j-1}} > 0,$ or $ g_{d_j}-(g_{d_{j-1}}+g_{d_{j-2}}) > 0,$ so we have $ a_i > a_{i-1} + a_{i-2}$ at the end and hence $ f(b) \in A.$ Thus, $ f: B \to A$ is well-defined.

In order to prove the injectivity of $ f,$ it suffices to prove each loop iteration as a mapping $ (c,a) \to (c’,a’)$ is injective, which would imply the mapping $ (c,0) \to (0,a)$ that the while loop creates is injective. Indeed, if $ f(b_1) = f(b_2) = a$ with $ (c_1, 0), (c_2, 0)$ being sent to $ (0, f(b_1)) = (0,a), (0, f(b_2)) = (0,a)$ respectively, then we have $ (c_1, 0) = (c_2, 0) \Rightarrow c_1 = c_2 \Rightarrow b_1 = b_2.$

Suppose $ d_1 > \dots > d_i, f_1 > \dots > f_j$ are the non-zero indices of $ c_1, c_2$ respectively and $ c_1 – (e_{d_1}+\dots+e_{d_i}) = c_2 – (e_{f_1}+\dots+e_{f_j}), a_1+g_{d_1}e_1 + \dots+ g_{d_i} e_i = a_2 + g_{f_1} e_1 + \dots + g_{f_j} e_j.$ If $ x \ge 2$ is an entry of $ c_1,$ it decreases by $ 1,$ so the corresponding entry in $ c_2$ after $ c_2$ is modified is also $ x-1,$ which means it must’ve been $ (x-1)+1 = x$ before since $ x-1>0.$ Thus, if the values of two positions of $ c_1, c_2$ differ, one is $ 1$ and the other is $ 0.$ However, if $ c_1 = (1,0), a_1 = (3,1), c_2 = (0,1), a_2 = (4,1),$ then $ (a_1, c_1), (a_2, c_2)$ both get sent to $ ((5,1), (0,0)).$ I can rule out this specific example by arguing that one of the pairs is illegal and could not have come from any choice of initial $ c,$ but I have no idea on how to do this in general.

What should I do next in order to show $ f$ is injective? Furthermore, since the problem I’m trying to prove is correct, injectivity would imply $ f$ is secretly a bijection. But I have no clue on how to even start on the surjectivity of $ f,$ so I just constructed a similar algorithm for $ g: A \to B$ in the hopes of proving $ g$ is injective too. If I can show $ f$ is injective I will probably know how to show $ g$ is.

Here is an example of $ f, g$ in practice:

Let $ n = 41, b = (12, 7, 7, 4, 4, 2, 2, 2, 1) \Rightarrow c = (1, 2, 2, 3, 1).$

$ $ ((1, 2, 2, 3, 1), (0,0,0,0,0)) \to ((0, 1, 1, 2, 0), (12, 7, 4, 2, 1)) \to ((0, 0, 0, 1, 0), (19,11,6,2,1)) \to ((21,11,6,2,1),(0,0,0,0,0)),$ $ so $ f(b) = (21,11,6,2,1).$

Let $ a = (21, 11, 6, 2, 1).$

$ $ ((21,11,6,2,1),(0,0,0,0,0)) \to ((9,4,2,0,0), (1,1,1,1,1)) \to ((2,0,0,0,0),(1,2,2,2,1)) \to ((0,0,0,0,0),(1,2,2,3,1)),$ $ so $ g(a) = (12, 7, 7, 4, 4, 2, 2, 2, 1).$